Proposed carbohydrate antigen 19-9 (CA19-9) cut-off values for the detection of pancreatic cancer in patients with poorly controlled diabetes: a real-world study - Taku Yamada; Taichi Minami; Masayo Yamada; Yasuo Terauchi (Endocrine Journal)
CA19-9 is a tumor marker for pancreatic cancer (PC), and the nondiabetic cut-off level is 37 U/mL. CA19-9 levels are said to rise in patients with tumors like PC and intraductal papillary mucinous neoplasm (IPMN). CA19-9 levels have also been shown to be related to HbA1c levels. We hypothesized that the CA19-9 cut-off levels would differ between patients with poorly controlled diabetes. This real-world trial was designed to test our hypotheses. This was a retrospective cohort study. All inpatients with poorly controlled diabetes had mean HbA1c levels of 10.0% and were divided into three groups: those with pancreatic cancer (PC group, N = 20), those with IPMN (IPMN group, N = 55), and those with neither (NC group, N = 985). Serum CA19-9 levels in the PC group were significantly higher than in the IPMN and NC groups (p < 0.001). CA19-9 levels did not differ statistically between the IPMN and NC groups. According to the receiver operating characteristic (ROC) analysis, serum CA19-9 levels of 98.4 U/mL had the highest sensitivity and specificity to detect PC, when comparing PC to IPMN + NC groups. Using this cut-off, the sensitivity and specificity of CA19-9 for PC were 70.0% and 96.5%, respectively, with a 0.81 area under the ROC curve. CA19-9 levels in two inpatients were >98.4 U/mL, most likely due to hepatocellular carcinoma and esophageal cancer. CA19-9 cut-off levels were thought to be 98.4 U/mL. However, we should keep in mind that the sensitivity and specificity were not 100%.